2019
DOI: 10.1016/j.isprsjprs.2019.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned Aerial System multispectral mapping for low and variable solar irradiance conditions: Potential of tensor decomposition

Abstract: Unlike satellite earth observation, multispectral images acquired by Unmanned Aerial Systems (UAS) provide great opportunities to monitor land surface conditions also in cloudy or overcast weather conditions. This is especially relevant for high latitudes where overcast and cloudy days are common. However, multispectral imagery acquired by miniaturized UAS sensors under such conditions tend to present low brightness and dynamic ranges, and high noise levels. Additionally, cloud shadows over space (within one i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Given this research-gap, current commercial multispectral cameras and data analysis (Michez et al 2019) have reported poor performances for pasture biomass estimation, both when employing spectral-based (R 2 = 0.35) or canopy based (photogrammetric estimated height) techniques (R 2 = 0.23). This is in spite of the potential reported in previous research (Mutanga and Skidmore 2004) and absence of scaling-up issues (Burkart et al 2014;Wang et al 2019).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Given this research-gap, current commercial multispectral cameras and data analysis (Michez et al 2019) have reported poor performances for pasture biomass estimation, both when employing spectral-based (R 2 = 0.35) or canopy based (photogrammetric estimated height) techniques (R 2 = 0.23). This is in spite of the potential reported in previous research (Mutanga and Skidmore 2004) and absence of scaling-up issues (Burkart et al 2014;Wang et al 2019).…”
Section: Introductionmentioning
confidence: 61%
“…In parallel, Burkart et al (2014) demonstrated the equivalence between spectral observations at two different data acquisition scales: handheld and low-level flight. In a more recent study, Wang et al (2019) presented a brief review on the difference between reflectance measurements from both acquisition-scales, indicating that such differences are negligible. Such findings fulfil a methodological gap for data collection, analysis and performance validation for UAV sensors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of uneven exposure of UAV images is also discussed in [26], however, this method focuses mainly on reducing distortions caused by cloud cover and variable solar irradiance conditions. This is a good method to reduce uneven lighting of images in a photogrammetric block when it is caused by shadows and external conditions during image acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the proposed solutions for solar and topographic corrections were based on approaches dedicated to satellite imagery [25]. Another approach suggests using tensor decomposition for solar corrections, however this method focuses mainly on reducing cloud distortion and variable solar irradiance conditions [26]. We notice in this manuscript that solar correction of low-altitude images requires a different approach.…”
Section: Introductionmentioning
confidence: 99%
“…UAS mapping under variable solar conditions also has an impact on image quality. Wang et al [155] proposed a pixel-wise radiometric and geometric calibration, extending the sensor calibration to such conditions and correcting vignetting effects. Stow et al [114] showed that illumination geometry impacts the retrieval of reflectance values, but using VIs and photogrammetry can mitigate those effects.…”
Section: Quality Assurance Metrics For Radiometric Datamentioning
confidence: 99%